2011
DOI: 10.1136/jmedgenet-2011-100218
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic spectrum associated with CASK loss-of-function mutations

Abstract: These findings define the phenotypic spectrum associated with CASK loss-of-function mutations. The combination of developmental and brain imaging features together with mild facial dysmorphism is highly suggestive of this disorder and should prompt subsequent testing of the CASK gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
160
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(182 citation statements)
references
References 18 publications
18
160
2
2
Order By: Relevance
“…52 A recent study reported renal/urologic anomalies, including fusion of kidneys, unilateral kidney ectasia, and malrotated kidney, in patients with CASK loss-of-function mutations. 53 Although these defects did not include our DKO phenotype of renal hypoplasia, they do suggest that scaffolding proteins may play an important role in congenital anomalies of the kidney and urinary tract (CAKUT). Because deletion of Cask alone in mouse nephron progenitors did not result in a kidney phenotype, we speculate that the renal anomaly observed in humans is the result of a combined effect with a variation in a protein that interacts with CASK, such as DLG1, Scribble, or the Lethal Giant Larvae homolog.…”
Section: Discussionmentioning
confidence: 99%
“…52 A recent study reported renal/urologic anomalies, including fusion of kidneys, unilateral kidney ectasia, and malrotated kidney, in patients with CASK loss-of-function mutations. 53 Although these defects did not include our DKO phenotype of renal hypoplasia, they do suggest that scaffolding proteins may play an important role in congenital anomalies of the kidney and urinary tract (CAKUT). Because deletion of Cask alone in mouse nephron progenitors did not result in a kidney phenotype, we speculate that the renal anomaly observed in humans is the result of a combined effect with a variation in a protein that interacts with CASK, such as DLG1, Scribble, or the Lethal Giant Larvae homolog.…”
Section: Discussionmentioning
confidence: 99%
“…Her neuroimaging demonstrates hypoplasia of the pons and cerebellar vermis, bowing and thinning of the corpus callosum, mild cerebral atrophy and dysplastic amygdala and hippocampi. This constellation of brain findings is reminiscent of the neurodevelopmental phenotype due to mutations in the CASK gene [Moog et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Calcium/calmodulin-dependent serine protein kinase (CASK) is one of the X-linked genes associated with syndromic mental retardation. [4][5][6][7][8][9] CASK mutations identified from patients are widely distributed across the entire gene, and no hot mutation spot in CASK linked to the disorder has been identified. 7,10 The phenotypes of patients with CASK mutations also vary.…”
Section: Introductionmentioning
confidence: 99%